PENGARUH KOMBINASI PIGMEN KURKUMIN-Î²-KAROTEN TERHADAP SPEKTRA ABSORPSI DAN NILAI SPF PADA SEDIAAN LOTION - Yanti, Ninda Meili; Alimuddin, Andi Hairil; Rahmalia, Winda (Indonesian Journal of Pure and Applied Chemistry, 2024)
This research aimed to examine the effect of the combined use of curcumin and Î²-carotene pigments on their absorption spectra. Subsequently, these pigment combinations were incorporated into a lotion formulation to determine their respective Sun Protection Factor (SPF) values. Mixtures of curcumin and Î²-carotene were prepared at mass ratios (w/w) of 0:5, 1:4, 2:3, 3:2, 4:1, and 5:0. Their absorption spectra were analyzed with a UV-Vis spectrophotometer over the 200"“600 nm wavelength range using ethyl acetate as the solvent. Then, 6% of each pigment mixture was incorporated into a lotion base. The results of the UV-Vis analysis revealed no significant spectral shifts across the various mixtures. However, a notable increase in absorption intensity (a hyperchromic effect) was explicitly observed for the 1:4 mass ratio of curcumin to Î²-carotene. The SPF values for the lotion samples containing 6% of the pigment mixtures were as follows: 5.02 (0:5), 8.32 (1:4), 8.63 (2:3), 8.10 (3:2), 8.14 (4:1), and 8.09 (5:0). Although the observed increase was not statistically significant, these findings suggest that the combination of curcumin and Î²-carotene pigments can enhance the SPF value relative to that of the individual components.